Letter (copy) : Basque children - Harries, E. P.
037-0135-001 EPH/FEA/1971 Organisation 11th June, 1937. Mr. R. Roberts, M.P., Basque Children Committee, 53, Marsham Street, S.W.1. Dear Mr. Roberts, BASQUE CHILDREN. I attach herewith letter I have received from Mr. Marshall Fraser of the Imperial Hotel, Blackpool. Mr. Marshall Fraser and his wife are prepared to take an active part in forming a local Committee in order either to raise funds for the Basque children or to secure suitable premises. Perhaps you will be good enough to consider the advisability of writing the Mayor of Blackpool and say you understand that there are sympathisers in the rown [town] who would be prepared to assist if he would be good enough to call a Town's Meeting on the subject. Kind regards. Yours sincerely, Secretary, Organisation Department. Letter. 292/946/37/135